Influence of Vanadium and Boron Additions on the Microstructure, Fracture Toughness, and Abrasion Resistance of Martensite-Carbide Composite Cast Steel - Waleed Elghazaly; R. Rashad; Sayed Elmohr; Saied Elghazaly (Advances in Materials Science and Engineering)
High chromium cast steel alloys are being used extensively in many industrial services where dry or wet abrasion resistance is required. Such steel castings are demanded for cement, stoneware pipes, and earth moving industries. In this research, five steel heats were prepared in 100 kg and one-ton medium frequency induction furnaces and then sand cast in both Y-block and final impact arm spare parts, respectively. Vanadium (0.5–2.5%) and boron (120–150 ppm) were added to the 18Cr-1.9C-0.5Mo steel heats to examine their effects on the steel microstructure, mechanical properties especially impact, fracture toughness and abrasion resistance. Changes in the phase transformation after heat treatment were examined using inverted, SEM-EDX microscopy; however, the abrasion resistance was measured in dry basis using the real tonnage of crushed and milled stoneware clay to less than 0.1 mm size distribution.